Investment Portfolio of Pension Funds: Regulation and Implementation - ., Alfiana; CM Simatupang, Ervina; Borshalina, ita (International Journal of Engineering and Technology, 2018)
This study determines which pension fund investments affect the return of investment in the pension fund industry. This research is an explanatory research conducted using multiple regression with data from the monthly pension fund statistics for the March 2015 to June 2018 period. The results show that of the 19 investments that the pension fund industry can make, there are still 2 types of investments that have not yet been made and 3 types of investments exceeding the limit specified allocation. In this study, only government bonds and land investments have a positive effect on return of investment while land and building investments have a negative effect. The results of this study indicate that the regulations do not have an impact on changing the type and allocation of investment in the pension fund industry, and is still dominated by certain investments that do not have an influence on the profitability of the pension fund industry which is measured by return of investment. Therefore, further studies are needed. This study is useful for (1) the pension fund industry to be able to apply investment portfolio theory regarding the types and allocations of investments and start new types of investment that are permitted (2) for financial services authorities (financial services authority) in order to arrange regulations regarding the type and allocation of investment.